Early detection of significant congenital heart disease: The contribution of fetal cardiac ultrasound and newborn pulse oximetry screening. (2nd February 2021) - Menahem, Samuel; Sehgal, Arvind; Meagher, Simon
Abstract : Fetal cardiac and newborn pulse oximetry screening has greatly facilitated the detection of cardiac abnormalities, which may be serious with potentially dire neonatal consequences. The prenatal diagnosis of a serious cardiac abnormality allows the attending obstetrician to organise the much safer in‐utero transfer of the fetus for delivery at a tertiary centre, particularly if there is evidence of a duct‐dependent lesion that may require the infusion of Prostaglandin E1 to maintain duct patency pending surgical intervention. Newborn pulse oximetry alerts the paediatrician that the baby may have a significant cardiac abnormality, which warrants further elucidation prior to discharge, rather than for the baby to represent unwell a few days later. Despite these advances, serious cardiac abnormalities may be missed on screening. Their detection then falls back onto the clinical acumen of the attending paediatrician/family physician to review the history, carefully elicit and evaluate the clinical signs further aided by whatever investigations that may be available at the birthing hospital, frequently less resourced than the tertiary centres. At the outset, a brief synopsis is provided of the clinical findings that may point to a cardiac abnormality. That is followed by a critical review of the accuracy of prenatal and newborn pulse oximetry screening with emphasis on the lesions that may be missed. Suggestions are made as to how to improve the diagnostic accuracy.